Proof of concept study for the detection and quantification of low molecular weight human serum proteomes using a miniature near-infrared spectrometer - Thulya, C. P. (2020)
Detection of serum proteomics is regarded as a laborious analytical exercise due to the complexity of serum samples, which have a dynamic range of high molecular weight fractions (HMWF) including albumin, immunoglobulins, transferrin, and lipoproteins and low molecular weight fractions (LMWF) such as cytokines, chemokines, and peptide hormones. Serum possesses biomarkers from several organ-specific pathological events, which leads to the variation in serum biochemistry. The LMWF often contains several disease-specific biomarkers, which are usually neglected in detection due to the high abundance of HMWF in serum. Here, we present a novel near-infrared spectroscopy (NIR) approach to detect low molecular weight serum biomarkers using the simplest and smallest amino acid unit, glycine as a reference molecule.